2017
DOI: 10.1111/cpf.12450
|View full text |Cite
|
Sign up to set email alerts
|

An extended high‐frequency ultrasound protocol for detection of vessel wall inflammation

Abstract: An extended ultrasound protocol for central neck and leg arteries could be of value for diagnosis of arteritis. In case of atypical vessel wall inflammation, other main diagnoses should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 19 publications
(34 reference statements)
1
14
0
1
Order By: Relevance
“…Areas of increased IMT (≥0.9 mm in CCA, ICA, SCA, and CFA; ≥1.2 mm in the aortic arc) without atherosclerotic plaques showed regular wall thickening of medium echogenicity. We have recently shown that an extended US protocol is of value for the assessment of giant cell arteritis ( 39 ) and Takayasu arteritis ( 28 ). In these diseases, US appearance of the vessel walls was characterized by a smooth, circumferential, homogenous increased IMT, with or without fibrotic stripes depending on different stages of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Areas of increased IMT (≥0.9 mm in CCA, ICA, SCA, and CFA; ≥1.2 mm in the aortic arc) without atherosclerotic plaques showed regular wall thickening of medium echogenicity. We have recently shown that an extended US protocol is of value for the assessment of giant cell arteritis ( 39 ) and Takayasu arteritis ( 28 ). In these diseases, US appearance of the vessel walls was characterized by a smooth, circumferential, homogenous increased IMT, with or without fibrotic stripes depending on different stages of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we showed that both increased IMT, the difference between vessel diameter and lumen diameter and Takayasu ultrasound index could be used as ultrasound activity parameters combined with vessel wall appearance. According to our previous study, it is important to use a standardized protocol including fixed points for measurements of inflammatory wall changes (Zachrisson et al, 2018). Park et al (2001) suggested that a vessel diameter exceeding 10 mm should indicate inflammatory activity and used it in follow-up studies.…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis was thought unlikely as the wall thickening was uniform, homogenous and circumferential and rather than heterogeneous and eccentric as expected with atherosclerotic plaque . TAK and GCA account for the vast majority of large vessel vasculitides, with GCA being 10 times more common than TAK . GCA may affect the large arteries including the aorta as is seen in this case, however, TAK is far more likely to involve the mesenteric arteries .…”
Section: Discussionmentioning
confidence: 50%
“…Differential diagnoses to consider include giant cell arteritis (GCA), also referred to as temporal arteritis, and atherosclerosis . Atherosclerosis was thought unlikely as the wall thickening was uniform, homogenous and circumferential and rather than heterogeneous and eccentric as expected with atherosclerotic plaque . TAK and GCA account for the vast majority of large vessel vasculitides, with GCA being 10 times more common than TAK .…”
Section: Discussionmentioning
confidence: 97%